Mindfulness: Action research examining the effectiveness of mindfulness in a Montessori small-group intervention setting - Sherman, Jennifer (My University, 2017)
The purpose of this action research was to examine the effectiveness of short, regular sessions of mindfulness practice in reducing math anxiety and increasing academic performance in elementary-age students in a Montessori elementary school. This research was conducted in small-group, pull-out settings using one- to three-minute mindfulness exercises. The students were interviewed at the beginning and end of the study to gauge their anxiety level regarding math and testing. Prior to the beginning of mindfulness practice, a lesson was taught that described the benefits of mindfulness and its effects on the human brain. Students evaluated their emotions at the end of each small-group session to determine whether mindfulness was having an effect in the short term.